Carbon Incentive Distribution in Review of Economic Benefit in Islam and Lucas Critique - Aptasari, Fety Widianti; Falah, Muhammad Helmi (Accounting and Finance Studies, 2024)
Research Aims: This research aims to review the allocation of carbon incentive funds through the concept of justice in Islam and Lucas' critique, with a focus on the application of carbon incentives in Islamic economic concepts. Design/methodology/approach: This research uses a qualitative approach with a descriptive exploratory method and a humanisteocentric approach to criticise the application of carbon incentives in the concept of Islamic economics and the concept of Lucas criticism. Research Findings: The results show that carbon incentive policies in the context of Islamic economics should be designed to ensure that economic benefits are distributed fairly and in line with the principles of justice and social welfare. Revenues from carbon incentives should be used to support programmes that help reduce economic inequality, protect the environment and empower communities. Theoretical Contribution/Originality: This research contributes to the literature by highlighting the importance of carbon incentive policy design that not only contributes to climate change mitigation, but also strengthens social and economic justice in accordance with Islamic teachings.